Genomic Profiling and Prognostic Value Analysis of Genetic Alterations in Chinese Resected Lung Cancer With Invasive Mucinous Adenocarcinoma - Cai, Lei; Wang, Jiangfeng; Yan, Junrong; Zeng, Jian; Zhu, Liang; Liang, Jinxiao; Pan, Chao; Huang, Xiancong; Jin, Ju; Xu, Yang; Wang, Fufeng; Shao, Yang; et al. (Frontiers in Oncology, 2021)
Background: Invasive mucinous adenocarcinoma (IMA) of the lung is a distinct histological subtype with unique clinical and pathological features. Despite previous genomic studies on lung IMA, the genetic characteristics and the prognosis-related biomarkers in Chinese surgically resected lung IMA remain unclear. Methods: We collected 76 surgically resected primary tumors of invasive lung adenocarcinoma, including 51 IMA and 25 non-mucinous adenocarcinomas (non-IMA). IMA was further divided into pure-IMA (mucinous features≥90%) and mixed-IMA subgroups. Comprehensive genomic profiling based on targeted next-generation sequencing (NGS) of 425 genes was explored and genomic characteristics were evaluated for the correlation with postoperative disease-free survival (DFS). Results: IMA had a unique genetic profile, with more diverse driver mutations and more tumor drivers/suppressors co-occurrence than that of non-IMA. The frequency of EGFR (72.0% vs. 40.0% vs. 23.1%, p=0.002) and ALK (undetected vs. 20.0% vs. 26.9%, p=0.015) alterations showed a trend of gradual decrease and increase from non-IMA to mixed-IMA to pure-IMA, respectively. The frequency of KRAS mutations in pure-IMA was higher than that in mixed-IMA, albeit statistically insignificant (23.1% vs. 4.0%, p=0.10). TP53 mutation was significantly less in pure-IMA compared to mixed-IMA and non-IMA (23.1% vs. 52.0% vs. 56.0%, p=0.03). Besides, IMA exhibited less arm-level amplifications (p=0.04) and more arm-level deletions (p=0.004) than non-IMA, and the frequency of amplification and deletion also showed a trend of gradual decrease and increase from non-IMA to mixed-IMA to pure-IMA, respectively. Furthermore, prognosis analysis in stage III IMA patients showed that patients harboring alterations in EGFR (mDFS=30.3 vs. 16.0 months, HR=0.19, P=0.027) and PI3K pathway (mDFS=36.0 vs. 16.0 months, HR=0.12, P=0.023) achieved prolonged DFS, while patients with poorly differentiated tumors (mDFS=14.1 vs. 28.0 months, HR=3.75, p=0.037) or with KRAS mutations (mDFS=13.0 vs. 20.0 months, HR=6.95, p=0.027) had shorter DFS. Multivariate analysis showed that KRAS mutations, PI3K pathway alterations, and tumor differentiation status were independent factors that have statistically significant influences on clinical outcomes of IMA patients. Conclusion: Our study provided genomic insights into Chinese surgically resected lung IMA. We also identified several genomic features that may serve as potential biomarkers on postoperative recurrence in IMA patients with stage III disease.